-35х-30-15=2-6х 0,7-2,3х+2=-0,8+1,7х
-35х-45=2-6х 2,7-2,3х-1,7=-0,8
-35х+6х=2+45 -2,3х-1,7х=-0,8-2,7
-29х=2+45 -4х=-0,8-2,7
-29х=47 -4х=3,5
х= х=0,875
3.0,5x-2(0,3x+0,8)=0,3(x-6)-0,4
0,5х-0,6х-1,6=0,3х-1,8-0,4
-0,1х-1,6=0,3х-1,8-0,4
-0,1х-0,3х-1,6=-2,2
-0,1х-0,3х-1,6=-2,2+1,6
-0,4х=-0,6
х=1,5
ответ:1) (5а+3)+(-3а-4)=5а+3-3а-4=2а-1
(5а+ 3)-(-3а-4)=5а+3+3а+4=8а+7
2) (7х2+3х)+(-2х-1)=7х2+3х-2х-1=7х2+ 1х-1
(7х2+3х)-(-2х-1)= 7х2+3х+2х+1=7х2+ 5х+1
3)( 8b2 + 2b - 4)+( 5 - 3b - 9b2)= 8b2 + 2b – 4+5 - 3b - 9b2=-b2-b+1
( 8b2 + 2b - 4)-( 5 - 3b - 9b2)= 8b2 + 2b – 4 -5+3b+9b2=17b2+ 5b-9
4) (11y - 12 - y3)+( 14 - 12y + y3)= 11y - 12 - y3+14 - 12y + y3=-y+y3+2
(11y - 12 - y3)-( 14 - 12y + y3)= 11y - 12 - y3-14+12y-y3=23y-2y3-26
5) (6 + mn + 2)+( 4 - mn - m2)= 6 + mn + 2+4 - mn - m2=12-mn-m2
(6 + mn + 2)-( 4 - mn - m2)= 6 + mn + 2-4+mn+m2=4+2mn+m2
Объяснение:
не благодарите
5a-18-12a+34=-7a+16
1,4c-7,2b-3,8b+2,6c=-11b+4c
2)a+(b+c-d-p)=a+b+c-d-p
a-(b+c-d-p)=a-b-c+d+p
2m-(n+m)+(m+n)=2m-n-m+m+n=2m
2,5p-(6+8p)=2,5p-6-8p=-5,5p-5
3)4(5-3x)+9x-7=20-12x+9x-7=13-3x
7x(2t+5)-23t-11=14xt+35x-23t-11
-3(0,7+1,4)+4,8-7,1p=-2,1-4,2+4,8-7,1p=-1,5-7,1p
5(6,1-4,2a)+6,3a-4,7=30,5-21a+6,3a-4,7=25,8-14,7a